2015
DOI: 10.1016/j.rbmo.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Causes, effects and molecular mechanisms of testicular heat stress

Abstract: The process of spermatogenesis is temperature-dependent and occurs optimally at temperatures slightly lower than that of the body. Adequate thermoregulation is imperative to maintain testicular temperatures at levels lower than that of the body core. Raised testicular temperature has a detrimental effect on mammalian spermatogenesis and the resultant spermatozoa. Therefore, thermoregulatory failure leading to heat stress can compromise sperm quality and increase the risk of infertility. In this paper, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
231
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(250 citation statements)
references
References 126 publications
(203 reference statements)
10
231
0
9
Order By: Relevance
“…It has been repeatedly demonstrated both in mammals and in fish that fertilization capacity can be preserved in spermatozoa showing standard quality in terms of motility and morphology although carrying a damaged genome (Upadhya et al 2010, Avendano & Oehninger 2011, Perez-Cerezales et al 2011, Fernandez-Diez et al 2015. Fertilization with DNA-damaged sperm increases the risk of promoting pregnancy loss in mammals (Speyer et al 2010), arrest in embryo development or embryo death (Perez-Cerezales et al 2010b, Gawecka et al 2013, birth defects, chromosomal abnormalities and other genetic diseases (Fernandez-Gonzalez et al 2008, Barroso et al 2009, Schulte et al 2010, Marchetti et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been repeatedly demonstrated both in mammals and in fish that fertilization capacity can be preserved in spermatozoa showing standard quality in terms of motility and morphology although carrying a damaged genome (Upadhya et al 2010, Avendano & Oehninger 2011, Perez-Cerezales et al 2011, Fernandez-Diez et al 2015. Fertilization with DNA-damaged sperm increases the risk of promoting pregnancy loss in mammals (Speyer et al 2010), arrest in embryo development or embryo death (Perez-Cerezales et al 2010b, Gawecka et al 2013, birth defects, chromosomal abnormalities and other genetic diseases (Fernandez-Gonzalez et al 2008, Barroso et al 2009, Schulte et al 2010, Marchetti et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization with DNA-damaged sperm increases the risk of promoting pregnancy loss in mammals (Speyer et al 2010), arrest in embryo development or embryo death (Perez-Cerezales et al 2010b, Gawecka et al 2013, birth defects, chromosomal abnormalities and other genetic diseases (Fernandez-Gonzalez et al 2008, Barroso et al 2009, Schulte et al 2010, Marchetti et al 2015. The DNA-repairing activity relies on the oocyte machinery once the fertilization takes place (Aitken et al 2014, Fernandez-Diez et al 2015, the zygote being responsible for repairing the sperm damage. In previous studies, we found that trout oocytes are able to repair at least 10% of sperm DNA fragmentation (Perez-Cerezales et al 2010) and demonstrated that the suppression of the repairing activity in trout zygotes, using an inhibitor of the Poli (ADP-ribose) polymerase (PARP) activity involved in the base excision repair (BER) pathway, has severe consequences for the progeny: alternative repairing mechanisms were activated, embryo survival was reduced and surviving larvae displayed massive differences in the transcriptomic profile (Fernandez-Diez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it alters the expression profiles of many genes [4,29,30]. In this regard, we previously showed high expression of heat shock 70 kDa protein 2 (HSPA2) in testicular tissue and caudal segment of epididymides in rat varicocele model [31].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for reduced expression of PLCζ could be related to oxidative stress. DNA and RNA are common targets of reactive oxygen species [37] which might have a critical effect on embryo quality and pregnancy rates in IVF/ICSI treatments [38][39][40] and increased upon heat stress or in varicocele condition [30,41].…”
Section: Discussionmentioning
confidence: 99%